Research and design of China Telecom BSS middle platform - Zhiqiong LIU; Na CHEN; Kaikai LIU; Zhuxuan HUA (Dianxin kexue)
The new business formats, new ecosystem cooperation challenges and opportunities brought by the transformation of communication technology in the 5G and cloud network integration era of telecom operators were analyzed.Combined with the current situation of China Telecom information construction, the construction scheme of enterprise middle platform which is suitable for China Telecom was put forward.Based on the construction idea of“light portal, variant application, stable middle platform”, the construction scheme of business platform was focused on.Through introducing application layer and building the middle platform, the fast and accurate response of front-end business and market were realized.And through the case introduction, the feasibility and superiority of the scheme was verified.